2021
DOI: 10.2147/ijgm.s300968
|View full text |Cite
|
Sign up to set email alerts
|

Influence of KDR Genetic Variation on the Efficacy and Safety of Patients with Chemotherapy Refractory Metastatic CRC Who Received Apatinib Treatment

Abstract: Background The aim of the present study was to investigate the influence of kinase insert domain containing receptor (KDR) genetic variation on the efficacy of treatment and safety of patients with chemotherapy-refractory metastatic colorectal cancer (CRC) receiving apatinib. Methods A total of 108 patients with chemotherapy refractory metastatic CRC who were treated with apatinib participated in this study retrospectively. Efficacy of the patients’ treatment was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…To the best of our knowledge, patients with ECOG higher score had a trend to correlate with worse prognosis regardless of the therapeutic regimens. 26 Therefore, the conclusion that ECOG performance status might be used as a potential biomarker might be confirmed in prospective clinical trials subsequently. Additionally, it was noteworthy that a total of 20 patients (24.1%) had received PD-1 blockades previously, which was strikingly different from the baseline characteristics in the ALTER1102 trial (patients rarely received PD-1 blockades administration).…”
Section: Discussionmentioning
confidence: 95%
“…To the best of our knowledge, patients with ECOG higher score had a trend to correlate with worse prognosis regardless of the therapeutic regimens. 26 Therefore, the conclusion that ECOG performance status might be used as a potential biomarker might be confirmed in prospective clinical trials subsequently. Additionally, it was noteworthy that a total of 20 patients (24.1%) had received PD-1 blockades previously, which was strikingly different from the baseline characteristics in the ALTER1102 trial (patients rarely received PD-1 blockades administration).…”
Section: Discussionmentioning
confidence: 95%
“…Herein, we found 14 genes with UTR variants, of which four cancer-associated genes harbor variants in 3′ UTR ( KDR and CARD11 ) and 5′ UTR ( CSMD3 and TLX3 ). These genes have been described as oncogenes, coding for vascular endothelial growth factor receptor 2 [ 57 , 74 , 75 ], promoting cell survival by activating NF-kb [ 76 , 77 ], activating downstream MAPK/ERK signaling, inhibiting p53 and activating cMyc [ 78 , 79 ], and promoting cell growth in hematological neoplasms by activating LINC00478/miR-125b [ 80 ]. The UTR variants can alter the binding site of miRNAs, impairing their regulatory capacity; they may also generate a new binding site for other miRNAs, resulting in an imbalance of cellular homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion suggested that CT/TT genotype of rs2305948 was correlated with an inferior prognosis than that of TT genotype among patients with extensive-stage SCLC. Additionally, a recent study initiated by Bai et al 12 included 108 patients with metastatic colorectal cancer and performed the exploration of the clinical impact of VEGFR2 4397T>C polymorphism. Results exhibited that patients with TT genotype of 4397T>C polymorphism predicted superior PFS and OS in patients with colorectal cancer who received apatinib administration.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Additionally, previous exploratory research suggested that polymorphism of VEGFR2 might be a promising biomarker that was dramatically associated with the prognosis of patients who were treated with antiangiogenic TKI. 12 Additionally, a recent study indicated that polymorphism of −906T>C in the VEGFR2 gene might be used as a potential biomarker to predict the prognosis of patients with osteosarcoma who were treated with apatinib monotherapy. 13 Unfortunately, to our knowledge, there were still no valuable polymorphism biomarkers that were available to predict the efficacy of anlotinib monotherapy among patients with treatment-refractory advanced NSCLC currently.…”
Section: Introductionmentioning
confidence: 99%